Spanish Confraternities of Our Lady of Mercy, the Redeemer of Captives in the Samogitian Diocese: History and Importance to Local Piety Traditions - Stankevičienė, Regimanta (Acta humanitarica academiae Saulensis, 2019)
The article has gathered and systematised data about the confraternities of Our Lady of Mercy and the Redemption of the Captives (Latin: Beatae Maria de Mercede) that were active in the Samogitian Diocese in the 18th and 19th centuries. After a short introduction of the religious order of Mercedarians, the founder of these confraternities, and the spread of the cult of Our Lady of Mercy in the Catholic Church promoted by the order, the article concentrated on the history of the said confraternities in Lithuanian Catholic churches and the scope of existing research as well as possible directions of further investigations.The Mercedarians themselves have never settled in the Polish-Lithuanian Commonwealth (Kingdom of Poland and the Grand Duchy of Lithuania) and, based on currently available data, the said confraternities only operated in the old Samogitian Diocese (its former area before the administrative and territorial reform that took place in the mid-19th century). Here, since the 1720s, 11 or 12 confraternities of Our Lady of Mercy have been founded in churches starting with the Diocese centre in Varniai: Varniai St. Alexander Church and parish churches or chapels of ease of Lioliai, Girkalnis, Šatės, Šakyna, Gardamas, Pakruojis, Kurtuvėnai, Judrėnai, Lieplaukė, Skirsnemunė and Pernarava (?). The popes and local bishops permitted to found them after the cult of Our Lady of Mercy spread outside the Mercedarian order: in 1696 pope Innocent XII extended the feast day of Our Lady of Mercy to the entire Catholic Church dedicating September 24 for this purpose. The main indulgence feasts of the said Samogitian confraternities were associated with this day (although there were exceptions) and the dates for other events of the confraternities used to be separately set by the local bishop. Indulgence feasts of the same title that used to be celebrated in several more churches and chapels of this diocese or historically related areas were likely influenced by these confraternities as well.These confraternities of Our Lady of Mercy have left some traces in the religious culture of the Samogitian Diocese and Marian art that need further research. The investigation of these confraternities in the Samogitian Diocese deepens our knowledge of the impact of the Spanish religious culture and art on the Catholic traditions of this Lithuanian region.
Keywords: Samogitian Diocese; confraternity; Our Lady of Mercy; the Redeemer of Captives (Latin: Beatae Maria de Mercede); Mercedarians